2022
DOI: 10.5194/acp-22-1825-2022
|View full text |Cite
|
Sign up to set email alerts
|

Simulated impacts of vertical distributions of black carbon aerosol on meteorology and PM<sub>2.5</sub> concentrations in Beijing during severe haze events

Abstract: Abstract. Vertical profiles of black carbon (BC) play a critical role in modifying the meteorological conditions such as temperature, planetary boundary layer height (PBLH), and regional circulation, which influence surface layer concentrations of PM2.5 (particulate matter with a diameter of 2.5 µm or less; the surface layer covers from 0 to 79.5 m). However, BC vertical profiles in current models usually have large uncertainties. In this study, by using measurements of BC vertical profiles in Beijing collecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…If this difference persists in the troposphere, the underestimated PM2.5 components might cause an underestimation of negative radiative forcing at TOA. The underestimation of BC and scatter aerosols might result in more solar radiation reaching the ground (Chen et al, 2022;Tang et al, 2022). This is consistent with the overestimation of maximum daily maximum temperature over the eastern regions (Zhu et al, 2020), likely serving as a positive feedback between negative aerosol biases and overestimated surface temperature.…”
Section: Discussionsupporting
confidence: 66%
“…If this difference persists in the troposphere, the underestimated PM2.5 components might cause an underestimation of negative radiative forcing at TOA. The underestimation of BC and scatter aerosols might result in more solar radiation reaching the ground (Chen et al, 2022;Tang et al, 2022). This is consistent with the overestimation of maximum daily maximum temperature over the eastern regions (Zhu et al, 2020), likely serving as a positive feedback between negative aerosol biases and overestimated surface temperature.…”
Section: Discussionsupporting
confidence: 66%
“…Notably, the surface BC concentrations observed over Delhi during this event exceeded those reported during severe haze episodes over the Beijing metropolis by nearly a factor of three. 63,64…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the surface BC concentrations observed over Delhi during this event exceeded those reported during severe haze episodes over the Beijing metropolis by nearly a factor of three. 63,64 Modelled AOD 550 nm is also compared against the AERONET observations at the Lahore and Kanpur sites in the upper and lower IGP, respectively (Fig. S4 †).…”
Section: Model Characterisation Of the Severe Pollution Episodementioning
confidence: 99%
“…The 2017 China smog event was an extreme air pollution episode that affected East China, initiated by slow air carrying industrial emissions and meteorological conditions, that took place in December of that year. High levels of PM 2.5 (generated from coal combustion and industrial sources) and low visibility were observed, leading to the closure of airports, highways, and schools [ 21 , 22 , 65 ]. For the simulation of a Beijing-like atmosphere, VOCs were introduced into the atmospheric chamber as precursors, which were the most abundant and commonly emitted particulates in the urban atmosphere of Beijing at the time: isopentane (alkane), propene (alkene), acetylene (alkyne), acetaldehyde (aldehyde), benzene, toluene, and m,p-xylene (aromatic hydrocarbons).…”
Section: Methodsmentioning
confidence: 99%